Effect of tool eccentricity on surface periodic banded structures in friction stir welding. Issue 1 (November 2015) - Guo, N; Wang, M R; Meng, Q; Zhou, L; Tang, D Y
Abstract: This paper describes the relationship between tool eccentricity and surface formation of periodic banded structures in friction stir welding. Motion characteristics of welding tool are calculated to explore the forming mechanism of banded structures. The results reveal that the welding tool motion differences on advancing side and retreating side caused by eccentricity are crucial for the formation of banded structures. The crests and troughs of banded structures form during tool motion on retreating side and advancing side, respectively.